2020
DOI: 10.1002/acr.24088
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Recovery Trajectories of Acute Flares in Knee Pain: A UK‐Netherlands Multicenter Prospective Cohort Analysis

Abstract: Objective. To identify distinct recovery trajectories of acute flares of knee pain and associated participant characteristics. Methods. Data were from the FLARE randomized controlled trial, a multicenter trial in 27 primary care centers in the UK and Netherlands of 3 regimes of oral nonsteroidal antiinflammatory therapy for acute flares of knee pain. Individuals with a history of inflammatory/crystal arthritis, fibromyalgia, and chronic pain syndrome were excluded. Latent class growth analysis was applied to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
2
3
0
1
Order By: Relevance
“…Further research is needed to confirm whether the cumulative frequency of flare episodes drives OA etiopathogenesis 43 . Our observed median 5-day flare duration, is broadly consistent with previous estimates 35 , 44 . The nature of trigger exposures and the duration of flare episodes are important insights for patient-healthcare professional consultations, particularly as our data suggest flares appear more common among working age adults.…”
Section: Discussionsupporting
confidence: 92%
“…Further research is needed to confirm whether the cumulative frequency of flare episodes drives OA etiopathogenesis 43 . Our observed median 5-day flare duration, is broadly consistent with previous estimates 35 , 44 . The nature of trigger exposures and the duration of flare episodes are important insights for patient-healthcare professional consultations, particularly as our data suggest flares appear more common among working age adults.…”
Section: Discussionsupporting
confidence: 92%
“…Results found in the validation sample effectively validated the decisions adopted with the derivation sample. When comparing our results to other studies, we found theoretical consistency in endorsed dimensions related to are in OA(8, 16), and methodological coherence in using self-report questionnaire, which proved useful for measuring the construct (4,24).…”
Section: Discussionsupporting
confidence: 72%
“…In step 7, local dependency between items was detected when a residual correlation was 0.2 point above the average of all items residual correlations (24). Local dependency was solved by combining items modalities into a super-item, a solution which involved a sum of the dependent items also called "subtest" (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thomas и соавт. [22] изучали обострения ОА у 449 пациентов. Главным признаком обострения считалось усиление боли ≥5 по числовой рейтинговой шкале (ЧРШ, 0-10).…”
Section: безрецептурные нестероидные противовоспалительные препараты unclassified